Energy consumption, environmental emissions and economic growth: an empirical analysis in Nigeria - Gambo, Suleman Lawal; Ishak, Suryati; Ismail, Normaz Wana; Muhammad Idris, Moukhtar (International Organization Of Scientific Research, 2018)
This study examined the relations of energy consumption, emissionsand economic growth as an important yardstick determining the level of economic activities in Nigeria. Using ARDL method to cointegration. The empirical results shown that in long and short-run analysis, we found the amounts of energy used have a significant and positive relationship with economic growth, this result shows that an increase in energy used Nigeria is highly interconnected with the gross domestic product as an indicator of economic growth while foreign direct investment and fossil fuel are negatively related to gross domestic products. Thus, we recommended that wind or solar source of energy might be discovered plus measured as a substitute basis of energy meanwhile Nigeria is sound gifted with the wind and solar energy. This will support in decreasing CO2 emissions in another hand to supporting growth in long run.